PENGARUH PDRB, JUMLAH PENDUDUK, INVESTASI DAN BELANJA MODAL TERHADAP PENERIMAAN PAJAK DAERAH DI PROVINSI KALIMANTAN TIMUR - Dimas Bagus Mahasinul Akbar (2022)
This research aims to determine the effect of Gross Regional Domestic Product (GRDP), Total Population, Investment and Capital Expenditure on local tax revenues in districts/cities in East Kalimantan Province. The data used is secondary data obtained from the Central Statistics Agency (BPS). This study uses panel data by combining time series and cross section data. The method in this study uses panel data regression analysis which can be used to measure the effect of the independent variable on the dependent variable. The results of this study indicate that population and investment have a significant positive effect, while GRDP and capital expenditures have no effect on local taxes. The results of the study simultaneously show that GRDP, population, investment and capital expenditures have an effect on local taxes.